Examining factors of physical activity participation in youth with spina bifida using the Theoretical Domains Framework. Issue 4 (October 2020) - Volfson, Zlata; McPherson, Amy C.; Tomasone, Jennifer R.; Faulkner, Guy E.; Arbour-Nicitopoulos, Kelly P.
Abstract: Background: Previous research has demonstrated that physical activity (PA) levels are lower for youth with Spina Bifida (SB) than their typically developing peers. However, there is a lack of understanding of the barriers to PA among this population. Objective/hypothesis: Using the Theoretical Domains Framework as a guide, the purpose of this study was to qualitatively explore the physical, psychological, social, and environmental factors influencing PA participation among youth with SB. Methods: Nine youth (six females; aged 14–17 years) took part in one, semi-structured individual interview. Transcripts were analysed using thematic analysis to identify barriers and facilitators to PA. Results: Youth identified social influences, impacts on general and mental health, positive affect, activity enjoyment and self-efficacy to be factors that facilitated their participation in PA. The most commonly reported barriers to PA were lack of knowledge, control over decision-making, inaccessible built environments, competing demands on time and pain/fatigue. Conclusion: These findings are the first step to identifying the most salient barriers and facilitators of PA for youth with SB. In turn, these factors can be further tested and targeted in future PA interventions.